START:AV in Incarcerated Young Adults: A Study of Psychometric Properties and Convergent Validity - Klimukienė, Virginija; Laurinavičius, Alfredas (Psichologija, 2025)
In the penitentiary system, criminal risk assessment aids in tailoring the resocialization process and informs decisions about detention conditions and eligibility for conditional release. Risk assessment instruments such as START:AV facilitate both the identification of the risk level and the planning of targeted interventions. The final judgment about the risk is based on the analysis of risk and protective factors, which differ by age, leading to the implementation of separate assessment instruments for adolescents and adults. The transition from adolescence to adulthood does not occur with the 18th birthday; therefore, there is an increasing emphasis on extending correctional measures applied to adolescents up to the age of 24. The aim of the study is to examine the psychometric characteristics and convergent validity of START:AV, designed for adolescents, in a sample of male offenders aged 18 to 23. The study involved 99 young individuals incarcerated in four prisons in Lithuania. Negative correlations found between START:AV strengths and vulnerabilities align with the findings of other studies and support the assumption that although they are related, yet, they remain distinct constructs. The Achenbach System of Empirically Based Assessment (ASEBA) Adult Self-Report (ASR) was used to assess the convergent validity of START:AV. The results confirmed that START:AV may be applicable for assessing the risk of adverse outcomes in incarcerated adults aged 18–23. Further studies on its predictive validity in the sample of emerging adults would be necessary to substantiate the practical utility of this instrument.
Keywords: young adults; incarceration; criminal behaviour; risk assessment; the START:AV